Study on 24 Jieling Drums as urban cultural landscape in Malaysia - Yunxi, Yang; Chow, Ow Wei (Logos Verlag Berlin, 2021)
The 24 solar terms, a knowledge system incorporated in the East Asian lunisolar calendar, reflect a typical agricultural life shaped by the astronomical and phenological nature in ancient China. The UNESCO’s Intangible Cultural Heritage embodies this Chinese tradition and culture. It is also commonly observed among Chinese diasporas in other parts of the world. Since 1988 when Tan Chai Puan and Tan Hooi Song established 24 Jieling Drums (二十四节令鼓) in Johor Bahru, Malaysia by exploring this Chinese traditional heritage, artistic performances of this vibrant music genre have effectively transmitted drumming aesthetics in Malaysian urban landscape into the Chinese cultural sphere for over three decades. This study explores a characterised link between this millennia-old Chinese cultural heritage and 24 Jieling Drums as an urban cultural landscape in Malaysia, and discusses several issues on the cultural elements applied in a diversified land through the narrative.